The Development of Investigative Learning Materials Using Computer Assisted Instruction in the Topic of Reflection for Grade VII - Kristanto, Yosep Dwi; Amin, Siti Maghfirotun; Khabibah, Siti (Universitas Muhammadiyah Surakarta, 2016)
Despite its importance, there are still many problems encountered in the learning of the topic of reflection in school. One of the solutions for these problems is the implementation of learning approaches that fit the modern curricula and the development of good quality instructional materials. Therefore, the aim of this study was to describe the quality of investigative instructional material with computer assisted instruction for the topic of reflection in Grade VII. The result of the analysis suggested that the investigative instructional material for the topic of reflection in Grade 7 is of good quality because it fulfills the following criteria: (1) the teacher was capable to manage the lesson well, (2) the students were actively involved during the lesson, (3) the students gave positive response to the instructional material, (4) the achievement test is valid, reliable, and sensitive; and (5) the validator claimed that the developed instructional material is valid.